Coal Transport Through The Conveyor Belt: Literature Study Of Process And Supporting Factors - Niken Devi Rosita (Nama Jurnal Akmi, 2023)
Transportation through sea transportation modes can be carried out to the side of the port and transported further by trucking mode or by other transportation systems, namely using a conveyor belt or belt conveyor that will deliver the cargo directly to the stockpile field or other places. A belt conveyor is a device that delivers bulk cargo to the destination of shelter or stacking. Transportation of one of the loads, namely coal using a conveyor belt by unloading the cargo using a crane to insert the cargo into the conveyor belt. Based on literature studies and field observations from research related to belt conveyor operations, supporting factors for the smooth operation of conveyors include belt width on the belt conveyor, type of idler, angular accuracy, gearbox speed, and density of each load. In addition, periodic maintenance and maintenance factors can reduce the risk of obstacles related to belt conveyor operations, including belts that suddenly jam, and loss of cargo (losses) causing losses and fines. Periodic maintenance and maintenance should be outlined in the Planning Maintenance System which must be complied with and needs to be supervised for implementation. Periodic audits are important to carry out the fulfillment of procedures in the field and checks on the condition of the equipment to minimize losses due to damaged equipment.